When babies read : a practical guide to help young children with hyperlexia, Asperger syndrome and high-functioning autism - Jensen, Audra, 1972- (Jessica Kingsley Publishers, 2005)
Audra Jensen' son began reading when he was only two years old. She shares her experiences - both the challenges and joys - of raising a child with autism and hyperlexia - an early and obsessive interest in the written word associated with social deficits and significant difficulty in understanding verbal language. The author stresses the importance of diagnosis of the condition for successful implementation of effective teaching strategies and encouragement of more typical childhood development. As well as useful advice, this guide provides a comprehensive reading curriculum specially designe.